THE INFLUENCE OF BUSINESS CITY ON THE BUSINESS ENVIRONMENT AND INFRASTRUCTURE (Innovate Conferences, 2025)
The concept of "business city" or business cities has emerged as one of the key trends in modern infrastructure development. A business city represents a comprehensive integration of office, commercial, residential, hotel, and other facilities that create a favorable environment for entrepreneurial activity. In the context of globalization and increasing competition, the establishment of business cities is becoming a crucial factor in stimulating regional economic activity and attracting investments.